2019
DOI: 10.1002/edn3.6
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and migration of the common shrimp, Palaemon paucidens in Lake Biwa, Japan—An eDNA‐based study

Abstract: Palaemon paucidens has a large population and is an important food source for fish in Lake Biwa, Japan. They are abundant in shallow waters from spring to summer, after which most individuals migrate to offshore deep areas where they remain during autumn and winter. However, some individuals are nonmigratory, remaining in shallow waters over winter. It has been reported that P. paucidens individuals have declined in recent years; a better understanding of its seasonal distribution is needed to manage this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Therefore, there may be a greater probability of detection using shorter amplicon assays relative to longer ones. While there is an increase in detection rates, previous studies have shown that assays targeting longer DNA fragments will selectively detect newly released eDNA (Jo et al., 2017; Wu et al., 2019), providing a more contemporary insight to fish community assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there may be a greater probability of detection using shorter amplicon assays relative to longer ones. While there is an increase in detection rates, previous studies have shown that assays targeting longer DNA fragments will selectively detect newly released eDNA (Jo et al., 2017; Wu et al., 2019), providing a more contemporary insight to fish community assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, target eDNA copy number is often found to correlate with species abundance in ponds and mesocosms (e.g., Lacoursière‐Roussel et al, 2016; Takahara et al, 2012), a correlation strengthened when allometric scaling is considered (Yates et al, 2021). Other recent studies have noted that the eDNA signal can vary spatially, revealing patterns of habitat use by target species (e.g., Oka et al, 2021; Wu et al, 2019). However, separating the signal of abundance from longitudinal information (i.e., where and when an organism was present) within these observations requires a deeper understanding of “eDNA ecology” (Barnes & Turner, 2016; Hansen et al, 2018), a term that encompasses rates of shedding, transport, and decay in the environment, and how these rates are influenced by various biotic and abiotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Because this method relies simply on collecting DNA fragments that exist in the water for analysis, it can be used to investigate biological population structures in a body of water without damaging the organisms and with a greatly decreased expenditure of time and labour. This technique has been widely used to investigate fish (Takahara et al, 2012; Thomsen et al, 2012), amphibians (Goldberg et al, 2011; Pilliod et al, 2013), reptiles (Davy et al, 2015; Hunter et al, 2015), crustaceans (Tréguier et al, 2014; Wu et al, 2019) and other organisms. Previous studies have shown that eDNA concentrations increase sharply during fish spawning periods (Buxton et al, 2017; Spear et al, 2015; Tsuji & Shibata, 2021).…”
Section: Introductionmentioning
confidence: 99%